Teaching co-cultural theory, dis/ability, and normativity using The Greatest Showman. Issue 2 (3rd April 2022) - Brown, Mary Kate; Chevrette, Roberta
Abstract : This unit activity guides students through an interrogation of bias, normativity, and co-cultural experiences within the context of dis/ability and appearance. Specifically, students complete implicit bias tests related to ability and body size, read about historical displays of bodily difference in circuses and "freak shows, " and then watch and discuss scenes from the film The Greatest Showman . In so doing, students engage in transformational learning that equips them to communicate more effectively with and about people with physical differences. Students develop their understanding of how cultural systems marginalize disabled bodies and think critically about how dis/ability intersects with other marginalized identities, including visible bodily differences, racial and ethnic identities, gender identities, and class identities. Courses : Intercultural Communication, Critical-Cultural Studies, Communication Theory, Rhetoric and Dis/ability. Objectives: This activity is designed to help students (1) critically reflect on cultural norms and their own and others' pre/misconceptions related to dis/ability and physical difference in an intersectional manner, (2) identify and comprehend co-cultural communication strategies, and (3) improve intercultural competence, including effectively communicating with and about people with dis/abilities and physical differences.